The Effect of Lecturer’s Competence And Learning Environment on Student’s Motivation in Learning English - Taufiqulloh, Taufiqulloh; Sulistianingsih, Endang; Aflahatun, Nur (Jurnal Bahasa Inggris, 2018)
The aimed of this study was to analyze the effect of lecturer’s competencies and learning environment on students’ motivation in learning English. This study used a verification method which used explanatory survey and correlation analysis with saturation sampling technique. The population of the study was the students of the social and political faculty at Universitas Pancasakti Tegal which amounts to 91 students. Primary data collection was done through the questionnaire which was distributed to respondents in this study. Data was analyzed through descriptive analysis, classical assumption test, and multiple regressions. The result of the simultaneous test indicated there was the significant effect of lecturer’s competence, learning environment and student’s motivation in learning English. Lecturer’s competence according to respondents was high, but the lecturers should always improve their pedagogic, personality, social and professional competencies. The university should provide a conducive learning environment and adequate teaching and learning facilities.